206k views
2 votes
Can someone solve this?

Can someone solve this?-example-1
Can someone solve this?-example-1
Can someone solve this?-example-2
User Matthias D
by
5.5k points

1 Answer

4 votes
  • First question:

Recall that
\cos^2x+\sin^2x=1 and
√(x^2)=|x| for all
x. So


√(1-\cos^2x)=√(\sin^2x)=|\sin x|


√(1-\sin^2x)=√(\cos^2x)=|\cos x|

For
0<x<\frac\pi2, we expect both
\cos x>0 and
\sin x>0 (i.e. the sine and cosine of any angle that lies in the first quadrant must be positive). By definition of absolute value,
|x|=x if
x>0.

So we have


(√(1-\cos^2x))/(\sin x)+(√(1-\sin^2x))/(\cos x)=(\sin x)/(\sin x)+(\cos x)/(\cos x)=1+1=\boxed{2}

making H the answer.

  • Second question:

C is always true, because the inequality reduces to x > y.

User Enrico Granata
by
5.5k points